ТАШКЕНТСКИЙ ГОСУДАРСТВЕННЫЙ СТОМАТОЛОГИЧЕСКИЙ ИНСТИТУТ ИСПОЛЬЗОВАНИЕ ИНТРАОРАЛЬНОГО СКАНЕРА В СОВРЕМЕННОЙ СТОМАТОЛОГИИ - Манукян, А.О.; Амануллаев, Р. А. (Educational Research in Universal Sciences, 2023)
Digital dentistry is actively developing. New technologies are growing every year that improve the quality of treatment, its comfort and the predictability of the clinical result. Such technologies include intraoral scanners with CAD/CAM detection and 3D impression printing. The purpose of this study was to test the effect of various types of intraoral scanners and 3D printers, as well as CAD/CAM systems, on the accuracy of printed models compared to plaster models obtained from conventional impressions.